PALEOEKOLOGI SATUAN BATULEMPUNG FORMASI JATILUHUR DAERAH CILEUNGSI , KECAMATAN CILEUNGSI, KABUPATEN BOGOR, JAWA BARAT - -, Lia Jurnaliah (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Claystone is composed of clay and carbonaceous sandstone. The relatively age of claystone is Lower Miocene (N8 Zone) – Middle Miocene (N9 Zone). Based on quantitative analysis of benthic foraminifer fossils from 10 samples on Cikarang river line, there are 31 species and 480 individuals, meanwhile, from 6 samples of Cilegok river line, are found 20 species and 348 individuals. Percentages of benthic foraminifer fossils on Cikarang River are 94,8% Rotaliina, 2,71% Textulariina, 2,71% Milioliina. Cilegok river has 98,28% Rotaliina, 0% Textulariina, 1,72% Miloliina.The interpretation of Paleoecology was done by using fossil assemblages, Diversity Index α Fisher and Triangular Plot Murray. Based on those methods, paleoecology of claystone of Jatiluhur Formation of Cileungsi area was Normal Marine Lagoons.